2001
DOI: 10.1007/s004640090126
|View full text |Cite
|
Sign up to set email alerts
|

Clonidine provides opioid-sparing effect, stable hemodynamics, and renal integrity during laparoscopic cholecystectomy

Abstract: Clonidine enabled stable hemodynamics and prevented activation of RAAS seen as unchanged plasma renin activity. Clonidine may be beneficial during laparoscopy in patients with hypertension, cardiovascular, and/or renal diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 20 publications
5
37
0
3
Order By: Relevance
“…Cardiac output was not changed in the clonidine group during CP, but decreased after release of CP [8]. Clonidine also was effective in reducing MAP and heart rate during laparoscopic cholecystectomy in the head-up position in another clinical trial, but no data were given regarding stroke volume or cardiac output [15]. Again, the possibility cannot be excluded that both esmolol as well as clonidine compromise physiologic reaction to compensate for hemodynamic changes of CP.…”
Section: Reducing Sympathetic Nerve Activitymentioning
confidence: 85%
“…Cardiac output was not changed in the clonidine group during CP, but decreased after release of CP [8]. Clonidine also was effective in reducing MAP and heart rate during laparoscopic cholecystectomy in the head-up position in another clinical trial, but no data were given regarding stroke volume or cardiac output [15]. Again, the possibility cannot be excluded that both esmolol as well as clonidine compromise physiologic reaction to compensate for hemodynamic changes of CP.…”
Section: Reducing Sympathetic Nerve Activitymentioning
confidence: 85%
“…Some procedures were feasible at 5–7 mm Hg [25, 26], but the required abdominal distension varies with surgical procedure, anatomical conditions and myorelaxation. The recommendation is to apply the lowest possible pressure level for each particular case.…”
Section: Cardiovascular Systemmentioning
confidence: 99%
“…[14] Various drugs have been compared with clonidine as pre-anaesthetic medications, mainly benzodiazepines such as midazolam [7] and diazepam, which show greater post-operative agitation. [10][11][12] Gabapentin did not show superiority in post-operative pain relief. Ketamine showed better post-operative pain relief, but also had a greater incidence of agitation and hypersalivation, [21] and magnesium sulphate showed no benefits with respect to clonidine.…”
Section: Discussionmentioning
confidence: 99%
“…[9] Various studies have reported on the use of clonidine as a pre-anaesthetic medication and have shown its effects on hemodynamic stability, postoperative pain, hypnosis-sparing, and nausea and vomiting reduction. [10][11][12][13] This study aimed to analyse the effect of clonidine on the target dose of propofol in total intravenous anaesthesia.…”
Section: Introductionmentioning
confidence: 99%